WESCML: A Data Standard for Exchanging Water and Energy Supply and Consumption Data. (2016) - Simons, Bruce A.; Yu, Jonathan; Leighton, Benjamin
Abstract: Improving data consistency and facilitating opportunities for cross-domain urban and rural research is important in order to understand patterns of development and for modelling urban and rural growth. Two key sectors are water and energy, and researchers and policy analysts have previously found it difficult to compare and contrast data in these industries. Variability in formats, spatio-temporal granularity, access methods and differing semantic definitions hinder attempts to access, analyse, interpret, compare and combine datasets. Through the AURIN Lens 6/2 project, we have developed a GML-based standard for exchanging Water and Energy Supply and Consumption (WESC) data, called the WESC Markup Language (WESCML-SF1), as an extension to the OGC/ISO Observation and Measurements (O&M) standard. Limitations of the consuming client applications required creating a simplified version that didn't incorporate O&M, the WESCML-SF0 information model. WESCML-SF0 and SF1 formalize definitions for the specific domain model features, along with related vocabulary definitions. This provides encoding of fine-scale WESC data for research and policy analysis in a consistent and machine consumable format that can be more readily discovered, accessed and used, rather than having users deal with multiple bespoke formats that impede data use and interoperability. WESCML-SF0 is using the Spatial Information Services Stack (SISS) for the necessary software components that support the provision of data in a federated information architecture via standard OGC web services. This allows greater ease of access to WESC data for a wider community of urban researchers, policy makers and managers.